2019
DOI: 10.14742/ajet.4117
|View full text |Cite
|
Sign up to set email alerts
|

ESOL pre-service teachers’ experiences and learning in completing a reflection paper and digital storytelling

Abstract: This qualitative study investigated how pre-service teachers of English for Speakers of Other Languages (ESOL) experienced and learned from their completion of a reflective project, including a reflection paper and digital storytelling. The participants were 20 graduate students in a program for Teaching English to Speakers of Other Languages (TESOL) at a university in the United States. This study aimed to identify participants’ experiences when completing the project and its influences on their learning. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 22 publications
(33 reference statements)
1
15
0
Order By: Relevance
“…The integration of vlog projects supports the learning goals and provides EFL learners with the opportunity to apply the knowledge acquired in classes to realworld workplaces (Hung, 2011). Through student-generated video filming learning projects, students are able to transform textbook knowledge into creative products with digital media literacy, problem-solving, collaboration and creativity, all of which align with 21st century skills in a changing world (Niemi & Multisilta, 2016;Oskoz & Elola, 2016;Park, 2019;Perry, 2018;Sousa, 2017). Vygotsky (1978Vygotsky ( , 1986 believed that social constructivism focuses on the social, cultural mechanisms of learning and knowledge construction.…”
Section: Literature Reviewmentioning
confidence: 99%
See 4 more Smart Citations
“…The integration of vlog projects supports the learning goals and provides EFL learners with the opportunity to apply the knowledge acquired in classes to realworld workplaces (Hung, 2011). Through student-generated video filming learning projects, students are able to transform textbook knowledge into creative products with digital media literacy, problem-solving, collaboration and creativity, all of which align with 21st century skills in a changing world (Niemi & Multisilta, 2016;Oskoz & Elola, 2016;Park, 2019;Perry, 2018;Sousa, 2017). Vygotsky (1978Vygotsky ( , 1986 believed that social constructivism focuses on the social, cultural mechanisms of learning and knowledge construction.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Students reported that they enjoyed a sense of achievement, and the video or vlog projects enhanced class engagement in terms of English learning (Aldukhayel, 2019;Gromik, 2012Gromik, , 2015. Finally, video-producing projects can help to improve literacy proficiency (McKenney & Voogt, 2011;Yang & Wu, 2012), enhance students' social skills while interacting with peers (Park, 2019), and promote active learning (Anas, 2019).…”
Section: Video Projects In Efl Learningmentioning
confidence: 99%
See 3 more Smart Citations